1998
DOI: 10.1111/j.1439-0426.1998.tb00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific immune response in fish fed glucan diets prior to induced transportation stress

Abstract: The present research studied the effects of feeding diets containing different doses of glucan on stress prevention in rainbow trout (Oncorhynchus mykiss). Different concentrations of glucan (0, 0.1, 0.5 or 1.0%) were administered to the fish over a 4-week period, then the fish were stressed by being transported for 2h. The effect of stress on the efficiency of the immune response was studied by measuring alterations of the following parameters: number and composition of the leucocyte population, phagocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
(3 reference statements)
0
16
0
1
Order By: Relevance
“…The combination of the stress challenge and YE supplementation completely prevented bacterial colonization of liver and air sac in this study, even though the stressed birds had been inoculated with low levels of E. coli at 1 wk of age. The ability of β-glucans to similarly modulate the effects of stress on the oxidative burst activity of fish neutrophils was previously reported (Jeney et al, 1997;Volpatti et al, 1998;Palic et al, 2006). β-Glucans, as well as β-glucan molecules from other sources, have been shown to increase oxidative burst Figure 3.…”
Section: Discussionmentioning
confidence: 88%
“…The combination of the stress challenge and YE supplementation completely prevented bacterial colonization of liver and air sac in this study, even though the stressed birds had been inoculated with low levels of E. coli at 1 wk of age. The ability of β-glucans to similarly modulate the effects of stress on the oxidative burst activity of fish neutrophils was previously reported (Jeney et al, 1997;Volpatti et al, 1998;Palic et al, 2006). β-Glucans, as well as β-glucan molecules from other sources, have been shown to increase oxidative burst Figure 3.…”
Section: Discussionmentioning
confidence: 88%
“…Immunostimulation is an important tool in aquaculture to increase resistance to pathogens [3] especially since substances, such as β-glucan, occur naturally in the environment and are thus less likely to raise concerns about residues in food fish and the environment [4]. Previous studies on β-glucan have highlighted a time and dose dependency of the effects [1,[33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of a more effective immune response to infectious agents by the use of dietary immunostimulant compounds has recently been demonstrated in several cultured fish species (Volpatti et al, 1998) and is a consequence of enhanced humoral and cell-mediated immune responses (Yano et al, 1991;Chen and Ainsworth, 1992;Siwicki et al, 1993;Verlhac et al, 1996). However, information on the effect of most immunostimulants on the activation of the non-specific immune response is still limited, particularly as far as lysozyme and complementmediated haemolytic activities are concerned (Hardie et al, 1990;Raa et al, 1992;Volpatti et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Many groups of substances are known to have an immunostimulant effect in terrestrial animals, but few of them have been shown to be effective in fish (Raa et al, 1992;Siwicki et al, 1998;Volpatti et al, 1998). These include glucans (structural elements of fungal cell walls) and nutritional factors such as ascorbic acid and a-tocopherol.…”
Section: Introductionmentioning
confidence: 99%